Experimental investigation of air heated bubble column humidification dehumidification desalination system. (16th September 2020) - Khan, Majid; Antar, Mohamed A.; Khalifa, Atia E.; Zubair, Syed M.
Summary: A novel configuration of humidification dehumidification (HDH) desalination system is presented using direct contact bubble column (BC) humidifier and dehumidifier. Experiments are carried out for performance analysis and comparison between a single‐stage, HDH air heated system (one humidifier and a dehumidifier) and a double‐stage HDH system (two BC humidifiers with air reheating). Effect of various operating parameters such as airflow rate, air temperature, and humidifier water levels is studied on performance metrics such as productivity, gain output ratio (GOR), input energy, specific energy consumption, and effectiveness. Results show that higher airflow rate, air temperature, and humidifier water level favor the system performance. The single‐stage system has a maximum productivity rate of 0.19 L/h and GOR of 0.21 obtained at 140°C and 1.5 standard cubic feet per minute (SCFM). However, the productivity of the single‐stage HDH system is limited due to low air outlet temperature at the exit of the BC humidifier. The double‐stage humidification system performs better in terms of productivity and GOR. The two‐stage humidification HDH system produced a distillate rate of 0.46 L/h and GOR of 0.4 with thermal energy increment of only 0.27 kW compared to the single‐stage system. The obtained results are promising in comparison with previous HDH studies, especially of air heated cycle. The estimated cost of production is 0.090 USD/L for double‐stage HDH BC.